Gestión técnica de riesgos mecánicos y ergonómicos en la empresa emvialrios e.p la Esperanza- Quevedo 2022 - Arévalo Vargas, Kerly Esthefanía (2022)
Abstract: The research work was carried out at the EMVIALRIOS EP Company, in charge of the construction of public works such as: streets, highways, roads or pedestrians and sports fields, the purpose of this project is to manage mechanical and ergonomic risks under a technical vision, identifying hazards, evaluating risks and carrying out corrective measures to prevent the various risk factors to which workers are exposed. There are 4 areas, where the GTC 45, Technical Guide was executed, reflecting 114 risks where 58.8% represent the mechanical risk factor and 48.2% ergonomic risk, for the respective evaluation, the William T. Fine matrix was used, where the presence of 61 risks was obtained, of which the percentage level of 23% is acceptable risk, 18% moderate, 45.9% notable risk, 9.8% high risk and 3.3% critical risk. According to the evaluations carried out using the Ergosoft Pro software with respect to the Reba method, it reflected 3 jobs with a medium risk level, 1 job with a low risk level for the left arm and medium risk for the right arm and 1 job of work with a low risk level, while in the Rosa method it was obtained: 10 jobs with a medium risk level and 3 jobs with a low risk level. Keywords: Evaluation, GTC 45, Identification, Technical Management, William T. Fine